Surgical management of tricuspid stenosis - Cevasco, Marisa; Shekar, Prem S. (Annals of Cardiothoracic Surgery, 2017)
Tricuspid valve stenosis (TS) is rare, affecting less than 1% of patients in developed nations and approximately 3% of patients worldwide. Detection requires careful evaluation, as it is almost always associated with left-sided valve lesions that may obscure its significance. Primary TS is most frequently caused by rheumatic valvulitis. Other causes include carcinoid, radiation therapy, infective endocarditis, trauma from endomyocardial biopsy or pacemaker placement, or congenital abnormalities. Surgical management of TS is not commonly addressed in standard cardiac texts but is an important topic for the practicing surgeon. This paper will elucidate the anatomy, pathophysiology, and surgical management of TS.